A comparison of the cost-effectiveness of intramedullary nail fixation and locking plate fixation in the treatment of adult patients with an extra-articular fracture of the distal tibia: Economic evaluation based on the FixDT trial. (May 2018) - Maredza, M.; Petrou, S.; Dritsaki, M.; Achten, J.; Griffin, J.; Lamb, S. E.; Parsons, N. R.; Costa, M. L.
Abstract : Aim: The aim of this study was to compare the cost-effectiveness of intramedullary nail fixation and 'locking' plate fixation in the treatment of extra-articular fractures of the distal tibia. Patients and Methods: An economic evaluation was conducted from the perspective of the United Kingdom National Health Service (NHS) and personal social services (PSS), based on evidence from the Fixation of Distal Tibia Fractures (UK FixDT) multicentre parallel trial. Data from 321 patients were available for analysis. Costs were collected prospectively over the 12-month follow-up period using trial case report forms and participant-completed questionnaires. Cost-effectiveness was reported in terms of incremental cost per quality adjusted life year (QALY) gained, and net monetary benefit. Sensitivity analyses were conducted to test the robustness of cost-effectiveness estimates. Results: Mean NHS and PSS costs were significantly lower for patients treated with an intramedullary nail than for those treated with a locking plate (-£970, 95% confidence interval (CI) -1685 to -256; p = 0.05). There was a small increase in QALYs gained in the nail fixation group (0.01, 95% CI -0.03 to 0.06; p = 0.52). The probability of cost-effectiveness for nail fixation exceeded 90% at cost-effectiveness thresholds as low as £15 000 per additional QALY. The cost-effectiveness results remained robust to several sensitivity analyses. Conclusion: This trial-based economic evaluation suggests that nail fixation is a cost-effective alternative to locking plate fixation. Cite this article: Bone Joint J 2018;100-B:624–33.